2017
DOI: 10.4236/jmp.2017.814135
|View full text |Cite
|
Sign up to set email alerts
|

Bifacial Silicon Solar Cell Steady Photoconductivity under Constant Magnetic Field and Junction Recombination Velocity Effects

Abstract: The paper reported a theoretical study on the photoconductivity of a bifacial silicon solar cell under polychromatic illumination and a constant magnetic field effect. By use of the continuity equation in the base of the solar cell maintained in a constant temperature at 300 K, an expression of the excess minority carriers' density was determined according to the applied magnetic field, the base depth and the junction recombination velocity. From the expression of the minority carriers' density, the photocondu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“… of illumination wavelength [20] [21] and illumination level n [22] [23] [24] or under dark [25];  of operating mode in particular, in static regime [26], the dynamic frequency regime [27] or transient dynamic regime [28] [29] [30]);  of external action by applied electromagnetic field [31] [32], or irradiation of nuclear particles [12] or a change in temperature [33]; In this work, the phenomenological parameters, such as the recombination velocity of the minority carrier in volume (τ), at the emitter-base junction (Sf) and at the rear face (Sb) of the thickness base (H), are studied. The optimum thickness (H) of the silicon solar cell base leading to the maximum short circuit current is determined according to the doping rate Nb (D), for a low level of illumination n. Figure 1 represents a silicon solar cell of type n + -p-p + under polychromatic illumination [34] [35].…”
Section: Introductionmentioning
confidence: 99%
“… of illumination wavelength [20] [21] and illumination level n [22] [23] [24] or under dark [25];  of operating mode in particular, in static regime [26], the dynamic frequency regime [27] or transient dynamic regime [28] [29] [30]);  of external action by applied electromagnetic field [31] [32], or irradiation of nuclear particles [12] or a change in temperature [33]; In this work, the phenomenological parameters, such as the recombination velocity of the minority carrier in volume (τ), at the emitter-base junction (Sf) and at the rear face (Sb) of the thickness base (H), are studied. The optimum thickness (H) of the silicon solar cell base leading to the maximum short circuit current is determined according to the doping rate Nb (D), for a low level of illumination n. Figure 1 represents a silicon solar cell of type n + -p-p + under polychromatic illumination [34] [35].…”
Section: Introductionmentioning
confidence: 99%
“…5) External conditions applied to solar cell i.e. : mono or polychromatic illumination [24], temperature (T) [25], electromagnetic field (E, B) [26], irradiation flow (ϕp) by charged particles [27].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on the photoconductivity, have been utilized for determining a few intrinsic parameters of semiconductors in different regimes, as: in transient one [4] [5], where a relationship between the photoconductivity, the average lifetime and the generation rate of the photogenerated minority carriers has led to determine the density of states as function of the temperature; in steady-state [6]- [12], without an applied magnetic field, the effective lifetime of the minority carriers is determined and then the photoconductivity according to the temperature, the generation rate and the incident light intensity, what permits to determine the recombination density of states. While, with an applied magnetic field, the photoconductivity is, on one hand, as function of the magnetic field and the junction recombination velocity [13] and on the other hand, as function of the wavelength, the magnetic field and the incident power [14] [15]. By the use of the Fermi-Dirac distribution, it is demonstrated that the electrical conductivity of a silicon material decreased with the electric field [16].…”
Section: Introductionmentioning
confidence: 99%